FISHING VESSEL ACTIVITIES AT NUSANTARA FISHING PORT OF PALABUHANRATU, WEST JAVA - Yarkuran, Mujiyati; Solihin, Iin; Bangun, Tri Nanda Citra (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
The Palabuhanratu Nusantara Fishing Port (PPN) is currently working to upgrade its status to Oceanic Fishing Port (PPS). The availability of infrastructure and supporting facilities is crucial to support this transformation process. The main activities at the Palabuhanratu PPN include ship berthing, distribution of logistical supplies, and ship repair services. However, crucial challenges often faced by this fishing port are suboptimal operational performance and the quality of services provided. This study aims to describe vessel activities, identify the growth rate of vessel activities, and formulate strategies to increase the number of vessel activities at the Palabuhanratu PPN. Data collection methods in this study involved interviews and direct field observations. Interview informants were determined using a random sampling technique. The collected data were then processed using descriptive analysis methods. The results of this study obtained four types of activities at the Palabuhanratu PPN: vessel arrival activities; loading and unloading activities; vessel supply activities; and ship repair activities. The growth rate of vessel activity at Palabuhanratu Port tends to fluctuate, with the highest number in 2012 at 903 units, and the lowest at 480 units in 2019. Strategies to increase vessel activity include optimizing port basin facilities through sediment dredging, improving the quality of human resources, and increasing fishermen's productivity. Key words: fishing ports, port operations, ship activities